A genome-wide shRNA screen uncovers a novel potential ligand for NK cell activating receptors - Romania, Paolo; Cifaldi, Loredana; Gragera, Paula; D’Alicandro, Valerio; Caforio, Matteo; Folgiero, Valentina; Lucarini, Valeria; Melaiu, Ombretta; Bei, Roberto; Locatelli, Franco; Fruci, Doriana (Frontiers in Immunology, 2025)
IntroductionNatural Killer (NK) cells play a key role in both innate and adaptive immune responses against viruses and tumor cells. Their function relies on the dynamic balance between activating and inhibitory signals, which are mediated by receptors that bind ligands expressed on target cells. While much is known about the function and expression patterns of NK cell activating receptors (NKARs), many of their ligands remain unidentified.MethodsK562 cells were transduced with a shRNA library targeting 15,000 genes and co-cultured with NK cells from healthy donors. Surviving clones were tested in cytotoxicity and degranulation assays. PLAC1 was cloned from JEG3 cells in a lentiviral vector and transfected in K562 cells. PLAC1-related gene expression and survival data were obtained from the TCGA database and analyzed using R. PLAC1 and DSG2 expression in healthy tissues and NK cells was obtained from the HPA database and a GEO dataset.ResultsWe identified ten candidate genes whose downregulation in K562 cells decreased NK cell-mediated cytotoxicity to levels comparable to silencing the MICA gene. The most promising candidates were functionally validated through single-target gene silencing and overexpression. Among them, the placenta-specific 1 (PLAC1) gene stood out, as its inhibition conferred the greatest protection to target cells from NK cell lysis, while overexpression of PLAC1 significantly increased NK cell degranulation. Importantly, PLAC1 was found to interact with NKAR fusion proteins, including NKG2D, DNAM1 NKp44 and NKp30, suggesting its potential involvement in NK cell function. PLAC1 is typically silent in normal tissues, with the exception of placental trophoblasts and testicular germ cells, but is markedly overexpressed in a wide range of tumors. Notably, its prognostic significance appears to be tumor-type specific, associating with either favorable or poor outcomes depending on the cancer context.DiscussionOur study identifies PLAC1 as a novel potential ligand for NKARs, suggesting it could be a valuable target for pharmacological strategies aimed at enhancing NK cell recognition. This finding holds promise for improving the efficacy of NK cell-based immunotherapies and advancing their clinical application.